A Review on Coronary Heart Disease Prevention: The Role of Nutrition, Foods, Dietary Patterns, and Oral Health in the Saudi Population - AlOtaibi, Nouf Naif; Alafaliq, Asma; Alsulayman, Wedyan Saleh; Alaslani, Mashael Ali; Alkhdery, Heba Khled; Alsamadani, Asmaa Ali; Alkhurayji, Munirah Saud; AlShehri, Aisha Mohammed; Handoud, Abdullah Hamad Al; Alshobromi, Abdalrahman Hamad (Journal of Posthumanism, 2024)
Coronary heart disease (CHD) is a leading cause of morbidity and mortality worldwide, and its prevalence is particularly high in Saudi Arabia, where lifestyle changes, including poor dietary habits and inadequate oral health, have significantly contributed to the rising burden of cardiovascular disease. This review examines the role of nutrition, dietary patterns, and oral health in preventing CHD in the Saudi population. It highlights the interrelationship between diet and oral health in the pathophysiology of CHD, emphasizing how nutrition can affect oral health and vice versa. The paper also discusses the importance of community-based interventions and policy recommendations to promote both heart-healthy eating and proper oral hygiene practices. The synergistic effect of these factors in reducing the risk of CHD is explored, alongside the critical role of healthcare professionals in delivering integrated care. The findings suggest that a holistic approach, addressing both dietary and oral health concerns, is essential for the effective prevention of CHD in Saudi Arabia. Further research and public health initiatives are necessary to implement such comprehensive strategies at a national level.